Integrated Community-Based Disaster Response Information System: A Case Study of the Subang Regency BPBD - Mohammad Iqbal; Erick Febriyanto; Rahmat Irsyada (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Subang Regency is an area highly prone to natural disasters such as floods, landslides, and strong winds. In emergency situations, the absence of an efficient and integrated reporting system greatly hinders Badan Penanggulangan Bencana Daerah (BPBD) in carrying out rapid responses, evacuations, and aid distribution. If not addressed promptly, public safety and the effectiveness of disaster management will remain at risk. Therefore, a disaster mitigation application system is needed that allows the community to quickly report disasters through photos, videos, and descriptions directly integrated with the BPBD dashboard. This application is equipped with multi-channel notifications via WhatsApp, SMS Gateway, and alarms, as well as an AI-based heatmap analytics system to predict potential disasters using historical data and weather information from BMKG. In addition, BPBD administrators can verify disaster reports by checking personal biodata linked to the reporter’s account. The system development method applied is Agile Development, which includes observation, planning, design, development, testing, and deployment, enabling intensive collaboration and rapid system iterations based on field feedback. With this system, BPBD Subang is expected to be more responsive and resilient in facing disasters.